Peran Baru dan Kewenangan Khusus Jakarta Pasca Pemindahan Ibu Kota Negara - Beni, Rozi (Jurnal Hukum & Pembangunan, 2024)
After the relocation of the National Capital to the Nusantara, Jakarta has a new role as the National Economic Center and Global City. This new role also becomes the basis for maintaining Jakarta's special status as the National Capital. Jakarta's new role and special authority are outlined in the Jakarta Special Regional Law (JSR Law). As a special region, Jakarta also has special authority. At the conceptual level, the regulation and management of Jakarta's special authority apply the types of administrative decentralization, political decentralization, and fiscal decentralization. Furthermore, in addition to changing its role as the National Economic Center and Global City, the JSR Law also regulates Jakarta's special authority covering several specific aspects in the fields of government affairs, institutions, personnel and regional finance. Jakarta's special role and authority must be carried out based on the relationship between authorities involving the central government, the JSR provincial government, and local governments in the agglomeration area. In its implementation, the JSR Law is expected to be an effective legal instrument to welcome the new era of Jakarta after the relocation of the National Capital. Not only to meet the legislative target stipulated in the National Capital Law, the law regulating Jakarta as the National Capital must be amended no later than February 24, 2024, so that the regulation of Jakarta's special authority is relatively limited and 'it is what it is' compared to the major role it must play as the National Economic Center and Global City.